2013
DOI: 10.1016/j.rmed.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic properties of C-reactive protein for detecting pneumonia in children

Abstract: CRP level has independent diagnostic value for pneumonia in children presenting at the ED with suspected pneumonia, but low levels do not exclude pneumonia in this setting. These results prompt evaluation of CRP in primary care children with LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
2
7
0
3
Order By: Relevance
“…In this regard, it is reasonable to conclude that serum CRP levels may be implicated in the etiology of pneumonia in newborn infants. In accordance with the results of the present meta-analysis, Koster et al measured the serum levels of CRP in children and found that serum CRP levels were independently correlated with pneumonia, indicating that the detection of serum CRP levels may have independent value in the diagnosis of pneumonia in children in an emergency department with potential pneumonia (24). Furthermore, Mintegi et al conducted a prospective multicenter study based on 188 children younger than 36 months cared for in pediatric emergency departments, and suggested that serum levels of CRP might be helpful in predicting the risk of occult pneumonia in infants with high fever without source (45).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this regard, it is reasonable to conclude that serum CRP levels may be implicated in the etiology of pneumonia in newborn infants. In accordance with the results of the present meta-analysis, Koster et al measured the serum levels of CRP in children and found that serum CRP levels were independently correlated with pneumonia, indicating that the detection of serum CRP levels may have independent value in the diagnosis of pneumonia in children in an emergency department with potential pneumonia (24). Furthermore, Mintegi et al conducted a prospective multicenter study based on 188 children younger than 36 months cared for in pediatric emergency departments, and suggested that serum levels of CRP might be helpful in predicting the risk of occult pneumonia in infants with high fever without source (45).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have identified the significant role of the serum CRP level in the development and prognosis of pneumonia, and have reported that an increased serum level of CRP may be present in patients with pneumonia (21,22). In particular, it has been found that the serum CRP level may be useful for distinguishing bacterial pneumonia from nonbacterial pneumonia in children, as higher serum CRP concentrations were observed in cases with a bacterial etiology (23,24). On the basis of this evidence, it may be hypothesized that the serum CRP level is closely correlated with the progress and severity of infant pneumonia (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…C-Reactive Protein (CRP) adalah salah satu penanda yang dapat dipakai untuk memprediksi infeksi bakteri, 12,13 merupakan suatu reaktan fase akut berukuran 23kDa, dihasilkan oleh hati yang dikontrol oleh Interleukin-6 (IL-6), dan mempunyai waktu paruh yang panjang (18)(19)(20) jam. Individu tanpa inflamasi biasanya memiliki kadar CRP <1 mg/L, dan kadar CRP bisa meningkat sampai 100 kali lipat kadar normal pada kasus inflamasi akut seperti infeksi, trauma, dan pembedahan.…”
Section: -11unclassified
“…Sensitivitas uji CRP, dengan cut off point 8 mg/L dan 10 mg/L hanya 51,6% dan 41,9%, menggambarkan kemampuan CRP yang rendah sebagai uji tapis. Koster dkk 19 dengan cut off point 10 mg/L mendapatkan hasil yang lebih tinggi, yaitu sensitivitas 90%, spesifisitias 40%, nilai prediksi positif 62%, dan nilai prediksi negatif 79%.…”
Section: Pembahasanunclassified
See 1 more Smart Citation